The Coconut Palm (Cocos nucifera L.) - Research and Development Perspectives (Springer Singapore, 2018)
Since the publication of "The coconut palm - A monograph" in 1960, considerable information has been accrued on the crop through work at research institutes, international organisations and development agencies. Although coconut cultivation is spread over 93 countries, providing employment and creating livelihood opportunities to 64 million families around the globe, smallholder coconut farmers are now facing numerous challenges. The wide gap between the potential and actual yield is a major concern, and as such it is necessary to disseminate knowledge in order to implement research findings. Coconut research in India, one of the leading coconut producing countries, is celebrating its centenary, making this an opportune time to review the research and development advances and the relevant technologies. This detailed, comprehensive book covers all aspects of coconut, from the origins to cultivation, breeding, physiology and value addition, as well as subjects of topical interest like nutrition and health, biotechnology, and climate change and carbon sequestration. Written by leading experts in the fields it emphasises that the livelihood of the small coconut landholders is the ultimate aim of scientists and developmental agencies, and outlines various important strategies to make coconut farming more remunerative globally. It discusses work in all the major coconut growing countries and outlines suggestions for international cooperation. Research work on the crop is comparatively difficult because of its perennial nature, longevity, height, long juvenile phase, large sized nuts, cross pollination and seed propagation. As these special features necessitate greater investment of resources, time and land, it is all the more imperative that research is not duplicated and the information and experience becoming available around the world is shared so that it can be fully utilised. In this context periodic publications, compiling all the available information on coconut assume greater significance. This book is therefore of great value to researchers, students, extension workers, developmental agencies and progressive farmers.